The Influence Of The Mixture Feed Kayambang (Salvinia Molesta D. S Mitchell) With Different Compositions To The Growth Of Sangkuriang Catfish (Clariass Spp) Enlargement Age (Grower) - Siti Diana Fathia; Soesy Asiah Susilawaty; Rini Solihat (Biology Education Department, Faculty of Teacher Training and Education, University of Nahdlatul Wathan Mataram - Indonesia, 2020)
Experimental research aims to determine the influence of mixed feed S. Molesta with different composition on the growth of Clarias Sp. The treatment carried out on this study included 3 different compositions of the S. Molesta flour is treatment A composition of the addition of S. Molesta is different from 20.62 grams (to reach A protein 30%), B treatment of S. Molesta composition given at 13.34 grams (to achieve protein 40%), and the treatment C composition of S. Molesta of 6, 05 gram (to reach protein 50%) and control (feeding factory F782). From the results of the study showed that the influence of artificial feed S. Molesta is best at treatment A and the lowest at the treatment of C. Based on research conducted the average weight increase Clarias SP is in the treatment of A 0.781 grams and the most significant increase in the length of the average in treatment A (30% protein) increased by 0.433 cm. Friedman test results show there is a difference in weight and length Clarias sp which is given the treatment of feed A, B and C and feed the plant (P > 0.05). The conclusion of the study was the influence of the feed mix S. Molesta to Growth Clarias SP age enlargement.